The criterion of individuation in the philosophy of Aristotle: Form or Matter? - mojtaba derayati (حکمت و فلسفه, 2015)
Abstract The discussion of the criterion of individuation has been an important and complex metaphysical debate in the history of philosophy and this is related with what its presence makes us to reach from the general or universal person to the fiddling person. The interpreters of Aristotle's philosophy are disagreeing about the criterion of beings individuation in his view. The most commentators believe that the form or matter and qualified matter or realized form in the opinion of others, is the criterion of individuation in Aristotle's view. In the beginning of this article, we will review the difference in application of  concepts such as individuation, identity and plurality in the texts of Aristotle. Although these three concepts are closely related to each other, but the commentators have been wrong in judging of criterion of individuation for incomprehension the difference between them. Then, we will study and review all terms of Aristotle's texts that various commentators resort or can resort to them in confirmation of their claim about the criterion of of individuation in Aristotle's view and we will show strengths and weaknesses of the various claims. Finally, we will discuss about this question that whether the criterion of individuation basically is an Aristotelian problem or not.